Solubility studies of prilocaine and lignocaine with Hydroxy-Propyl beta Cyclodextrin - Munot, Vaishaali (Curtin University, 2007)
Formulation of local anaesthetics in different dosage forms, including those for oral, parenteral, and topical application have being widely investigated. All of these formulations include local anaesthetics in their salt forms. The lipophilic nature of the bases of local anaesthetics may influence the rate of the pharmacological effect. There has been very little research done towards this aspect of local anaesthetics. Prilocaine base and lignocaine base possess greater lipophilicity than their salts. The salt forms undergo dissociation in the body. To maximise the absorption rate lipophilicity plays an important role. The aim of the present study is to evaluate the potential of using prilocaine and lignocaine individually and in combination as bases for parenteral formulations using cyclodextrins as complexing agents. Cyclodextrins are widely used as complexing agents to increase the solubility of poorly soluble drugs. Hydroxypropyl-β-cyclodextrin (HPβCD) was the first choice amongst the different cyclodextrins to be evaluated as a solubility enhancer as it does not show nephrotoxicity and is more bio-available compared to other cyclodextrins.Method: Prilocaine base was prepared from its salt and lignocaine base was obtained from Sigma Pharmaceuticals. Solubilities were examined individually and in combination by the phase solubility method and complex formation investigated. The mobile phase used was methanol:water (55:45) with phosphate buffer at pH 5.5. An AL type solubility isotherm was obtained for the influence of HPβCD on the solubilities of prilocaine and lignocaine. Complexation was investigated for both prilocaine and lignocaine to HPβCD by NMR. Results: The measured solubilities of prilocaine and lignocaine individually at 30% HPβCD from 25°C to 42°C were 1.96-7.91 moles/L and 1.69-4.55 moles/L respectively. The solubilities in combination were 0.91-3.68 moles/L for prilocaine and 1.03-8.35 moles/L for lignocaine respectively. The NMR data suggested that complexation involves the aromatic ring for both prilocaine and lignocaine apart from methene and methyl groups for prilocaine and ethyl amide and aromatic methyl groups for lignocaine.